Cerium‐Complex‐Catalyzed Oxidation of Arylmethanols under Atmospheric Pressure of Dioxygen and Its Mechanism through a Side‐On μ‐Peroxo Dicerium(IV) Complex. Issue 12 (19th February 2016) - Paul, Mitali; Shirase, Satoru; Morimoto, Yuma; Mathey, Laurent; Murugesapandian, Balasubramanian; Tanaka, Shinji; Itoh, Shinobu; Tsurugi, Hayato; Mashima, Kazushi
Abstract: Invited for the cover of this issue is the group of Hayato Tsurugi and Kazushi Mashima at the University of Osaka. The image depicts a cerium complex with a dianionic pentadentate ligand acting as a catalyst for aerobic oxidation of arylmethanols, in which a dinuclear cerium(IV) side‐on peroxo complex is the key intermediate. The corresponding trivalent complex was able to activate dioxygen, and the oxidation proceeded catalytically under atmospheric pressure with inexpensive and environmentally friendly dioxygen as the primary oxidant. Read the full text of the article at 10.1002/chem.201503846 . Abstract : " Thus, our big surprise was that the dioxygen dicerium complex worked as a catalyst for producing arylaldehydes from the corresponding alcohols, and the redox chemistry of Ce III /Ce IV was closely related to the catalyst performance of the Cu I /Cu II system ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 4008 ff. (DOI: 10.1002/chem.201503846 ).